Logistical Asia The Labour of Making a World Region (Springer Singapore, 2018)
This book explores how the management science of logistics changes working lives and contributes to the making of world regions. With a focus on the port of Kolkata and changing patterns of Asian regionalism, the volume examines how logistics entwine with political power, historical forces, labour movements, and new technologies. The contributors ask how logistical practices reconfigure both Asia's relation to the world and its internal logic of transport and communication. Building on critical perspectives that understand logistics as a political technology for producing and organizing space and power, Logistical Worlds tracks how digital technologies and material infrastructure combine to remake urban and regional territories and produce new forms of governance and subjectivity. Brett Neilson is Professor at the Institute for Culture and Society at Western Sydney University. With Sandro Mezzadra, he is author of Border as Method, or, the Multiplication of Labor (2013). With Ned Rossiter, he has coordinated the project Logistical Worlds: Infrastructure, Software, Labour. Ned Rossiter is Professor of Communication with a joint appointment in the Institute for Culture and Society and the School of Humanities and Communication Arts at Western Sydney University. His most recent book is Infrastructure, Software, Labor: A Media Theory of Logistical Nightmares (2016). Ranabir Samaddar is Distinguished Chair in Migration and Forced Migration Studies at the Calcutta Research Group. His research focuses on migration and refugee studies, nationalism and post-colonial statehood, and new regimes of technological restructuring and labour control. His most recent book is Karl Marx and the Postcolonial Age (2017).